A functional composite perovskite quantum dot material and its preparation method and application
By adding water-absorbing functional resin to perovskite quantum dot materials and depositing metal oxide films using ALD technology, the stability problem of perovskite quantum dot materials under water and oxygen intrusion is solved, and the material is high stability and widespread application.
Patent Information
- Application Number
- CN202111572431.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-12-21
AI Technical Summary
The invasion of water oxygen in the perovskite quantum dots in the actual environment leads to fluorescence quenching, brightness attenuation and optical color point changes, which have stability problems.
Water-absorbing functional resin is added to perovskite quantum dot materials, and a metal oxide film is deposited on the surface of powder particles through atomic layer deposition (ALD) technology to form a double-layer protective structure to improve water and oxygen resistance.
It significantly improves the stability of perovskite quantum dot materials, extends the retention time of its optical properties, and expands its application range.
Smart Images

Figure CN116285945B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a functional composite perovskite quantum dot material and a preparation method and application thereof, belonging to the field of material technology. Background Art
[0002] Perovskite quantum dots have excellent characteristics such as simple preparation process, low cost, high quantum yield, and high color purity. They can greatly improve the display color gamut of display devices, and therefore have received widespread attention. At present, thin films based on in-situ preparation of perovskite quantum dots have been successfully commercialized in the display field, which can increase the color gamut of display devices to more than 110% NTSC. In addition, perovskite quantum dot materials also have potential applications in fluorescent inks, optical anti-counterfeiting and other fields, and have received widespread attention. However, in practical applications, there are certain problems with the long-term stability of perovskite quantum dots, that is, the intrusion of water and oxygen in the actual environment causes fluorescence quenching, brightness attenuation and optical color point changes in quantum dots. Therefore, there is a need for a method to improve the water and oxygen barrier properties of perovskite materials, thereby improving the stability of perovskite quantum dots.
[0003] Using polymer materials to completely coat perovskite quantum dots is an effective method to enhance the stability of perovskite. Currently, polymer-coated perovskite quantum dots include two forms: in-situ coating and non-in-situ coating. The non-in-situ coating method is to first prepare perovskite quantum dots and then perform a subsequent polymer coating process (patents CN 110373180 A, CN106753328 A, CN 110511739). The byproducts produced by these post-treatment processes will cause the ligands on the surface of the quantum dots to fall off, affecting the optical properties and stability of the quantum dots. Moreover, perovskite quantum dots are difficult to disperse well in the polymer matrix, affecting the effect. Summary of the invention
[0004] According to one aspect of the present application, a functional composite perovskite quantum dot material is provided, wherein the powder particles contain a water-absorbing functional resin, which effectively improves the water and oxygen barrier properties of the powder particles and enhances the stability of the perovskite quantum dots.
[0005] A functional composite perovskite quantum dot material, comprising powder particles and a metal oxide film;
[0006] The powder particles contain surface ligands-perovskite quantum dots, matrix polymers and water-absorbing functional resins;
[0007] The metal oxide film is coated on the surface of the powder particles by atomic layer deposition.
[0008] Among them, surface ligand-perovskite quantum dots refer to the perovskite quantum dots with ligands coordinated on their surface.
[0009] Optionally, the water-absorbing functional resin includes at least one of resins containing a hydrophilic group.
[0010] Optionally, the hydrophilic group includes at least one of a carboxylic acid group, a sulfonic acid group, a hydroxyl group, and an ether group.
[0011] Optionally, the water-absorbing functional resin includes at least one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, polyvinyl pyrrolidine, and sodium polyacrylate.
[0012] Optionally, the mass ratio of the surface ligand-perovskite quantum dots, the matrix polymer and the water-absorbing functional resin is 0.1-1:1-100:0.1-100.
[0013] Optionally, the perovskite quantum dots in the surface ligand-perovskite quantum dots have at least one of the structural formulas ABX3, A3B2X9, and A2BX6; the ligand in the surface ligand-perovskite quantum dots has the structural formula CX;
[0014] Wherein A is selected from NH2CHNH2 + 、CH3NH3 + , Cs + , Rb + , K + At least one of;
[0015] B is selected from Pb 2+ Sn 2+ 、Bi 3+ 、Ti 3+ 、Zn 2+ 、Ni 2+ 、Cd 2+ 、Al 3+ , Mn 2+ , Mn 4+ ,Ge 3+ At least one of;
[0016] C is selected from an aromatic group or an alkyl organic amine cation having a carbon number of not less than 3;
[0017] X is selected from Br - ,I - 、SCN - , and at least one of carboxylate.
[0018] Optionally, the matrix polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride and trifluoroethylene copolymer, polyacrylonitrile, polyvinyl acetate, cellulose acetate, cyanocellulose, polysulfone, aromatic polyamide, polyimide, polycarbonate, polystyrene, polymethyl methacrylate, and polylauryl methacrylate.
[0019] Optionally, the powder particles are obtained by the following steps:
[0020] Atomizing a powder particle precursor solution into small droplets, and then drying the atomized small droplets to generate powder particles;
[0021] The powder particle precursor solution comprises a solvent, a surface ligand-perovskite quantum dot precursor raw material, a matrix polymer, and a water-absorbing functional resin.
[0022] Optionally, the solvent includes at least one of dimethyl sulfoxide, n-hexane, cyclohexane, n-octane, octadecene, ethanol, methanol, trimethyl phosphate, triethyl phosphate, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, isopropanol, ethyl acetate, toluene and acetone.
[0023] Optionally, the surface ligand-perovskite quantum dot precursor raw material includes AX, BX m and CX;
[0024] Wherein A is selected from NH2CHNH2 + 、CH3NH3 + , Cs + , Rb + , K + At least one of;
[0025] B is selected from Pb 2+ Sn 2+ 、Bi 3+ 、Ti 3+ 、Zn 2+ 、Ni 2+ 、Cd 2+ 、Al 3+ , Mn 2+ , Mn 4+ ,Ge 3+ At least one of;
[0026] C is selected from an aromatic group or an alkyl organic amine cation having a carbon number of not less than 3;
[0027] X is selected from Br - ,I - 、SCN - , carboxylate;
[0028] m=2, 3 or 4.
[0029] Optionally, the AX, BX m The molar ratio of CX is 0.5-10:1:0.3-10.
[0030] Optionally, the AX, BX mThe molar ratio of CX is 0.5-5:1-5:0.3-5.
[0031] Optionally, the AX, BX m The molar ratio of CX is 0.5~3:1~3:0.3~3.
[0032] Optionally, in the powder particle precursor solution, the volume mass ratio of the solvent to the matrix polymer is 300 ml: 1-50 g.
[0033] Optionally, in the powder particle precursor solution, the volume mass ratio of the solvent to the matrix polymer is any value of 300ml:1g, 300ml:10g, 300ml:20g, 300ml:30g, 300ml:40g, 300ml:50g, and a range value between any two values.
[0034] Optionally, the mass ratio of the surface ligand-perovskite quantum dot precursor raw material to the matrix polymer is 0.01-1:1-100.
[0035] Optionally, the mass ratio of the surface ligand-perovskite quantum dot precursor raw material to the matrix polymer is 0.01-1:1-50.
[0036] Optionally, the mass ratio of the surface ligand-perovskite quantum dot precursor raw material to the matrix polymer is 0.01-1:1-40.
[0037] Optionally, the mass ratio of the water-absorbing functional resin to the matrix polymer is 0.02-2.
[0038] Optionally, the mass ratio of the water-absorbing functional resin to the matrix polymer is any value of 0.02, 0.05, 0.1, 0.2, 0.5, 0.8, 1, 1.5, 2, and a range value between any two values.
[0039] Optionally, the mass ratio of the water-absorbing functional resin to the matrix polymer is 0.04 to 0.5.
[0040] Optionally, the mass ratio of the water-absorbing functional resin to the matrix polymer is 0.04 to 0.2.
[0041] Optionally, the conditions for atomization include:
[0042] Solution feed rate: 50~50000ml / h;
[0043] The corresponding atomizer air intake pressure is 0.02-1MPa, and the air intake speed is 15-100L / min.
[0044] Optionally, the drying conditions include: air inlet temperature: 50-200°C.
[0045] Optionally, the metal oxide in the metal oxide film includes at least one of Al2O3, TiO2, HfO2, and ZrO2.
[0046] Optionally, the metal oxide film has a thickness of 1 nm to 200 nm.
[0047] Optionally, the powder particles have a particle size of 0.1 to 50 microns.
[0048] According to another aspect of the present application, a method for preparing the functional composite perovskite quantum dot material described in any one of the above is provided, the preparation method comprising the following steps:
[0049] The raw materials containing metal precursor, oxygen precursor and powder particles are subjected to atomic layer deposition reaction to obtain the composite material.
[0050] Optionally, the metal precursor includes at least one compound containing a metal element.
[0051] Optionally, the metal precursor includes at least one of trimethylaluminum, aluminum trichloride, titanium tetrachloride, titanium isopropoxide, tetrakis(dimethylamino)zirconium, hafnium tetrachloride, hafnium nitrate, and dimethylaminozirconium.
[0052] Optionally, the oxygen precursor includes at least one substance containing an oxygen element.
[0053] Optionally, the oxygen precursor includes at least one of water, ozone and oxygen.
[0054] Optionally, the preparation method comprises the following steps:
[0055] (S1) introducing a gaseous metal precursor into a reaction chamber containing powder particles for adsorption;
[0056] (S2) introducing a gaseous oxygen precursor to carry out a reaction.
[0057] Optionally, the temperature in the reaction chamber is 40-100° C., and the vacuum degree is 0.1-300 Torr.
[0058] Optionally, the flow rates of the gaseous metal precursor and the gaseous oxygen precursor are 10 to 500 standard milliliters per minute.
[0059] Optionally, the time of the adsorption and the reaction are independently 5 to 60 seconds.
[0060] Optionally, the adsorption is static adsorption.
[0061] Optionally, during the adsorption and reaction process, the powder is dispersed by at least one of rotating, stirring and vibrating the bin.
[0062] Optionally, after the adsorption is completed, the following step is further included: introducing a carrier gas to flush out the remaining precursor and by-products.
[0063] Optionally, the carrier gas includes at least one of inert gases.
[0064] Optionally, the carrier gas is introduced for a time of 10 to 60 seconds.
[0065] Optionally, steps (S1) to (S2) are repeated 1 to 500 times.
[0066] According to another aspect of the present application, there is provided an application of the composite material described in any one of the above items, or the composite material prepared by the preparation method described in any one of the above items in the field of backlight display, Micro / Mini LED direct display, lighting or photovoltaic light conversion materials.
[0067] The present application invents the addition of functional resins such as water absorbent during the in-situ preparation of perovskite quantum dot / polymer powder, and the use of ALD technology to plate a metal oxide film on the powder surface. The two layers of protection jointly improve the water and oxygen barrier properties and the stability of the perovskite quantum dot / polymer composite material.
[0068] The ALD technology in the present invention is widely used in the industry and has mature technology. The method can continue to deposit nanometer-thick or submicron-thick metal oxide films on the surface of uniformly dispersed perovskite quantum dots / polymer powders to complete the surface coating process of the entire microsphere.
[0069] The entire ALD coating process does not affect the optical properties of the perovskite quantum dot / polymer composite material itself.
[0070] The ALD-coated perovskite quantum dot / polymer powder in the present invention shows ultra-high resistance to solvent corrosion and water and oxygen resistance, improves the environmental stability of the polymer substrate, improves the stability of the quantum dot / polymer composite material, and expands the application range of the composite material.
[0071] This patent proposes that in the method of preparing perovskite quantum dots / polymer powder by spray drying, functional resins such as water-absorbing resins are added in situ to the precursor to absorb water vapor and other substances harmful to perovskite quantum dots that penetrate into the powder in time to avoid affecting the perovskite quantum dots. Secondly, after obtaining the perovskite quantum dots / polymer powder, the atomic layer deposition (ALD) technology is used to deposit a dense layer of metal oxide on the surface of the powder particles to prevent the intrusion of substances such as water and oxygen, which serves as the first protective layer of the powder particles and improves the stability of the perovskite quantum dots / polymer micropowder.
[0072] In order to achieve the above object, the present invention adopts the following technical solution, the solution process is as followsFigure 1 As shown: Perovskite quantum dots / polymer powder with functional resin added is prepared by spray drying technology, and then oxide film is deposited on the powder surface by ALD technology to complete the coating process. The structural diagram of the sample after coating is shown in Figure 2 The entire implementation process includes the following steps:
[0073] Perovskite quantum dot / polymer powder with added functional resin is prepared using spray drying technology. The in-situ coating method is to dissolve the raw materials of perovskite quantum dots together with the polymer, and evenly disperse the raw materials of perovskite quantum dots in the polymer. Then, after a high-temperature process, the perovskite quantum dots are generated in situ and dispersed in the polymer matrix, which can effectively completely coat the perovskite quantum dots. The preparation process of spray drying is as follows. Prepare the raw material solution: add the matrix polymer solution and the functional resin to the perovskite quantum dot raw material solution to form a powder particle precursor solution; spray drying process: the precursor solution is formed into atomized micro-droplets by a two-fluid atomizer through an infusion pipeline and enters the drying tower. After being dried by hot air blown in from the air inlet, perovskite quantum dot / polymer powder is formed, and the perovskite quantum dot polymer micro-powder enters the cyclone separator through the air outlet at the bottom of the drying tank to achieve powder collection.
[0074] The precursor solution is prepared by mixing a perovskite quantum dot precursor raw material, a matrix polymer, a functional resin and an organic solvent, and then stirring and dissolving them.
[0075] The perovskite quantum dot precursor raw materials include synthetic raw materials for preparing perovskite quantum dots. The synthetic raw materials for perovskite quantum dots include AX, BX t and a CX precursor; wherein A is selected from NH2CHNH2 + (FA + )、CH3NH3 + (MA + ), Cs + , Rb + , K + At least one of; B is selected from Pb 2+ Sn 2+ 、Bi 3+ 、Ti 3+ 、Zn 2+ 、Ni 2+ 、Cd 2+ 、Al 3+ , Mn 2+ , Mn 4+ ,Ge 3+ At least one of; C is selected from an aromatic group or an alkyl organic amine cation having a carbon number of not less than 3; X is selected from Br - ,I - 、SCN -, carboxylate; m = 2, 3 or 4;
[0076] The molar ratio of the perovskite quantum dot precursors AX, BXt and CX is 0.5-10:1:0.3-10;
[0077] The matrix polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride and trifluoroethylene copolymer, polyacrylonitrile, polyvinyl acetate, cellulose acetate, cyanocellulose, polysulfone, aromatic polyamide, polyimide, polycarbonate, polystyrene, polymethyl methacrylate, and polylauryl methacrylate.
[0078] The functional resins include high molecular compounds with hydrophilic groups such as carboxylic acid groups, sulfonic acid groups, hydroxyl groups, ether groups, etc., such as polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, polyvinyl pyrrolidine, sodium polyacrylate, and other types of functional resins.
[0079] The organic solvent may be at least one of dimethyl sulfoxide, n-hexane, cyclohexane, n-octane, octadecene, ethanol, methanol, trimethyl phosphate, triethyl phosphate, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, isopropanol, ethyl acetate, toluene and acetone.
[0080] The volume mass ratio of the solvent to the matrix polymer in the perovskite quantum dot precursor polymer solution is 100 ml: 1-100 g. The mass ratio of the quantum dot precursor raw material to the matrix polymer is 1: 1-200. The mass ratio of the matrix polymer to the functional value is 100: 1-50.
[0081] The spray drying process is achieved by a spray drying device with a two-fluid atomizer. The main process parameters include: solution feed rate: 50ml / h~50000ml / h; corresponding atomizer inlet pressure: 0.02~1MPa, inlet speed: 15L / min~100L / min; dryer inlet air temperature: 50~200℃.
[0082] The obtained perovskite quantum dot / polymer powder is dried to remove excess organic solvent at a drying temperature of 50-120° C. and a drying time of 30 min to 24 h.
[0083] The perovskite quantum dot / polymer powder has a size of 0.1 to 50 microns.
[0084] The ALD coating steps are as follows: Pour the dried perovskite quantum dot / polymer powder into the ALD equipment reaction chamber, set the ALD process parameters such as deposition temperature, reaction source pulse pressure and pulse number, cycle number, etc. according to the type of oxide film to be deposited, and then fill the metal precursor and oxygen precursor into the reaction chamber in the form of alternating pulses, repeat the cycle until the required deposition thickness is reached, and the ALD coating is completed.
[0085] The powder is poured into the ALD equipment reaction chamber, which operates in a chamber body rotation dispersion mode or high-speed mechanical stirring and mechanical vibration mode to ensure powder dispersion. During operation, the entire reaction chamber is gradually heated to 40-100 degrees Celsius.
[0086] The volume of the powder loaded into the reaction chamber does not exceed 1 / 3 of the total volume of the reaction chamber, and the mass of the loaded powder is 1 to 50 g.
[0087] A gaseous metal precursor is introduced into the reaction chamber and kept static to allow the metal precursor to be fully adsorbed on the polymer matrix. Subsequently, a carrier gas is introduced into the reaction chamber to flush and remove the remaining precursor and reaction by-products.
[0088] An oxygen precursor is introduced into the reaction chamber to react with the metal precursor adsorbed on the surface of the polymer matrix, and then a carrier gas is introduced into the reaction chamber to flush and remove the remaining precursor and reaction byproducts, thereby completing the first layer of metal oxide atomic layer coating.
[0089] The two reaction precursors are charged in cycles for multiple times, and the thickness of the metal oxide gradually increases until the set thickness is reached, completing the powder coating process.
[0090] The oxide films deposited by the ALD technology include metal oxide films such as Al2O3, TiO2, HfO2, and ZrO2.
[0091] The deposition thickness of the metal oxide is 1 nm to 200 nm.
[0092] The metal precursor refers to a compound raw material containing a metal element, including trimethylaluminum, aluminum trichloride, titanium tetrachloride, titanium isopropoxide, tetrakis(dimethylamino)zirconium, hafnium tetrachloride, hafnium nitrate, dimethylaminozirconium and other precursors.
[0093] The oxygen precursor refers to a raw material containing oxygen, including water, ozone, oxygen and the like.
[0094] The flow rates of the metal precursor and the oxygen precursor are 10 to 500 standard milliliters per minute, and the flow rate of the carrier gas is 10 to 1000 standard milliliters per minute.
[0095] The deposition mode of the reaction source and the powder is a static mode, that is, the precursor is kept in the reaction chamber for 5 to 60 seconds, the precursor is fully adsorbed on the polymer surface, and then the carrier gas is introduced to flush out the remaining precursor and by-products.
[0096] The carrier gas filled in is high-purity nitrogen or argon.
[0097] The gas flushing time after each reaction is 10s to 60s, and the flow rate of the flushing gas is 10 to 1000 standard milliliters per minute.
[0098] The present invention discloses a technology for in-situ preparation of functional composite perovskite quantum dot polymer powder using spray drying technology, wherein functional resins such as water absorption are added to the precursor to prepare the powder, and an oxide film is deposited on the surface of the powder using ALD technology, effectively improving the water and oxygen barrier properties of the powder particles, improving the stability of the perovskite quantum dots, and expanding the application range of the perovskite quantum dot powder. The method comprises the following steps: a perovskite quantum dot precursor solution is mixed with a matrix resin and a functional resin, and a perovskite quantum dot / polymer powder is prepared by spray drying technology; then, an atomic layer deposition (ALD) technology is used to deposit a metal oxide film on the surface of the perovskite quantum dot / polymer powder to complete the surface coating process of the powder particles.
[0099] The beneficial effects of this application include:
[0100] (1) The functional composite perovskite quantum dot material provided in the present application contains a water-absorbing functional resin in the powder particles, which effectively improves the water and oxygen barrier properties of the powder particles and enhances the stability of the perovskite quantum dots.
[0101] (2) The functional composite perovskite quantum dot material provided in the present application is obtained by coating a dense metal oxide film on the surface of powder particles using ALD technology, thereby improving the stability of the powder particles and expanding the application range of the polymer material. BRIEF DESCRIPTION OF THE DRAWINGS
[0102] Figure 1 : Schematic diagram of the process flow of this application.
[0103] Figure 2 : Schematic diagram of the structure of the sample coated on the polymer surface by ALD technology. 1 represents the surface ligand-perovskite quantum dots. 2 represents the matrix formed by the mixture of matrix polymer and functional resin; 3 represents the nano- or submicron-scale oxide layer coated by atomic layer deposition.
[0104] Figure 3 : Photograph of the surface ligand-perovskite quantum dots / polymer powder prepared in Example 1.
[0105] Figure 4:Photoluminescence spectrum of surface ligand-perovskite quantum dots / polymer powder
[0106] Figure 5 : Scanning electron microscopy images of surface ligand-perovskite quantum dots / polymer powders prepared by spray drying.
[0107] Figure 6 : Scanning electron microscope image of powder after ALD deposition coating.
[0108] Figure 7 : Comparison curve of the luminescence brightness attenuation of the powder after adding sodium polyacrylate and ALD coating and the untreated modified powder with aging time.
[0109] Figure 8 : Schematic diagram of the device for preparing surface ligand-perovskite quantum dots / polymer powder by spray drying in the embodiment of the present application.
[0110] Figure 8 1. Precursor tank 2. Atomizer 3. Drying tower
[0111] 4. Cyclone separator 5. Powder outlet 6. Induced draft fan
[0112] 7. Solvent recovery port 8. Condensation tower 9. Hot air blower DETAILED DESCRIPTION
[0113] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0114] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0115] The SEM images were obtained using a Hitachi SU8220 cold field emission scanning electron microscope.
[0116] The fluorescence emission spectrum was obtained by using a spectrocolorimeter from Admesy, and the excitation light source was a 455nm blue LED.
[0117] The process flow diagram of ALD coating in this application is as follows Figure 1 shown.
[0118] The schematic diagram of the structure of the sample coated on the polymer surface by the ALD technology in this application is as follows Figure 2 As shown, 1 represents the surface ligand-perovskite quantum dots; 2 represents the matrix formed by the mixture of the matrix polymer and the functional resin; and 3 represents the nano- or submicron-scale oxide layer coated by atomic layer deposition.
[0119] The schematic diagram of the device for preparing surface ligand-perovskite quantum dot / polymer composite powder material by spray drying in this application is as follows Figure 8As shown. The surface ligand-perovskite quantum dot precursor solution is placed in a precursor tank (1), and the surface ligand-perovskite quantum dot precursor solution is atomized into small droplets in a drying tower (3) by an atomizer (2). The hot air produced by the hot air blower (9) is passed into the drying tower to dry the atomized small droplets to generate surface ligand-perovskite quantum dot / polymer composite material ultrafine powder. The surface ligand-perovskite quantum dot / polymer composite material ultrafine powder generated in the drying tower and the solvent vapor enter the cyclone separator (4) for dry-wet separation, and the surface ligand-perovskite quantum dot / polymer composite material ultrafine powder is collected by the powder outlet (5) below the cyclone separator. The moisture in the cyclone separator enters the condensation tower (8) through the induced draft fan (6) to condense the solvent, and the solvent is collected by the solvent recovery port (7), and the air is discharged. The spray drying method is used to in-situ prepare surface ligand-perovskite quantum dot / polymer composite material ultrafine powder raw materials to generate products, the solvent is recyclable, and no waste gas is discharged throughout the process, which reduces the cost of the product and meets environmental protection requirements.
[0120] The molecular weights of the polymers used in the specific examples are as follows:
[0121] The molecular weight of polymethyl methacrylate is 30,000 to 200,000.
[0122] The molecular weight of sodium polyacrylate is 3000~7000000.
[0123] The molecular weight of polyethylene glycol is 1000 to 10000.
[0124] The molecular weight of polyvinylidene fluoride is 100,000 to 1,000,000.
[0125] Embodiment 1:
[0126] In this embodiment, tetrapropylammonium bromide-MAPbBr3 perovskite quantum dot precursor raw material and matrix polymer polymethyl methacrylate and water-absorbing functional resin sodium polyacrylate are selected for spray drying to prepare composite powder. 0.58g of surface ligand-perovskite quantum dot precursor raw material (composed of MABr, PbBr2, tetrapropylammonium bromide, molar ratio of 1mmol: 1mmol: 0.4mmol) is dissolved in 300ml of N, N dimethylformamide (DMF), and then 15g of polymethyl methacrylate and 1g of sodium polyacrylate are added to form a precursor solution (that is, the mass ratio of sodium polyacrylate and polymethyl methacrylate added is 0.067). After 2 hours of stirring and dissolving, spray drying is performed to prepare powder. The spray drying parameters are set as the feed rate of the solution is 500ml / h, the inlet pressure is 0.08MPa, the inlet speed is 60L / min, and the dryer inlet air temperature is 85 degrees Celsius.
[0127] The prepared surface ligand-perovskite / polymer powders are as follows Figure 3 As shown, the powder is bright green and its luminescence spectrum is Figure 4 At this time, the scanning electron microscope photo of the surface ligand-perovskite quantum dots / polymer powder is shown as Figure 5 As shown, the powder particle size is 5 microns.
[0128] Dry 10g of powder at 70℃ for 2 hours, and then perform atomic layer deposition coating. Put the powdered product into the reaction chamber of the ALD equipment, control the rotation and stirring (speed is 20r / min) while evacuating the chamber (vacuum degree is 1torr), and then heat the chamber to 70 degrees Celsius; introduce gaseous trimethylaluminum into the powder reaction chamber for 10 seconds to allow it to fully contact and adsorb on the powder surface, and then pass inert gas to remove excess trimethylaluminum and by-products for 60 seconds; introduce gaseous water into the chamber for 10 seconds to allow it to fully react with the trimethylaluminum on the surface of the particles. At this time, the two precursors react to generate the first atomic layer. The operation is repeated for 300 cycles, and the thickness of the oxide layer gradually increases until the surface coating process of the entire polymer powder is completed. The scanning electron microscope photograph of the powder after coating is shown in the figure. Figure 6 As shown in the figure, it can be seen that the surface structure has changed. This is the Al2O3 oxide layer deposited by ALD, with a thickness of 60nm.
[0129] The optical stability of the surface ligand-perovskite quantum dot / polymer powder before and after coating was evaluated. The uncoated powder and the powder coated with functional resin and ALD were encapsulated between two layers of PET film and placed in an environmental test chamber at 60°C and 90% RH for aging experiments. After 200 hours of aging, the brightness decay is as follows: Figure 7 As shown in the figure, after 350 hours of aging, the brightness of the powder after adding functional resin and ALD coating was only 5%, while the attenuation ratio of the untreated sample exceeded 25%. This proves that adding functional resin to quantum dot / polymer powder and ALD coating oxide film on the surface significantly improves the stability of perovskite quantum dots.
[0130] Example 2.
[0131] In this embodiment, tetrabutylammonium bromide-FAPbBr3 perovskite quantum dot precursor raw materials and matrix polymer polymethyl methacrylate and water-absorbing functional resin polyethylene glycol are selected for spray drying, 0.67g surface ligand-perovskite quantum dot precursor raw materials (composed of FABr, PbBr2, tetrabutylammonium bromide, molar ratio of 1.1mmol: 1mmol: 0.5mmol) are dissolved in 300ml of N, N dimethylformamide, and then 20g polymethyl methacrylate and 1g polyethylene glycol are added to form a precursor solution (that is, the mass ratio of polyethylene glycol to polymethyl methacrylate is 0.05), and after 2 hours of stirring and dissolving, spray drying is performed to prepare powder. The spray drying parameters are set as a solution feed rate of 500ml / h, an inlet pressure of 0.08MPa, an inlet speed of 60L / min, and a dryer inlet air temperature of 90 degrees Celsius.
[0132] The prepared surface ligand-perovskite / polymer microsphere powder is bright green. 1g of powder was dried at 70°C for 2 hours, and then coated by atomic layer deposition. The powdered product was placed in the reaction chamber of the ALD equipment, and the rotation stirring (speed of 30r / min) was controlled while vacuuming (vacuum degree of 1torr), and then the chamber was heated to 75 degrees Celsius; gaseous trimethylaluminum was introduced into the powder reaction chamber for 5 seconds to allow it to fully contact and adsorb with the powder surface, and then inert gas was passed to remove excess trimethylaluminum and by-products for 60 seconds; gaseous water was introduced into the cavity for 5 seconds to react with the trimethylaluminum on the surface of the particles. At this time, the two precursors reacted to generate the first atomic layer. The operation was repeated for 150 cycles to obtain a powder coated with an aluminum oxide layer with a thickness of about 30nm.
[0133] Example 3
[0134] In this embodiment, dodecyl dimethyl benzyl ammonium bromide-CsPbBr3 perovskite quantum dot precursor raw materials and matrix polymer polyvinylidene fluoride, water-absorbing functional resin polyethylene glycol are selected for spray drying, 0.73g surface ligand-perovskite quantum dot precursor raw materials (composed of CsBr, PbBr2, dodecyl dimethyl benzyl ammonium bromide, molar ratio of 1mmol: 1mmol: 0.4mmol) are dissolved in 300ml of N, N dimethylformamide, and then 25g polyvinylidene fluoride and 2g polyethylene glycol are added to form a precursor solution (that is, the mass ratio of polyethylene glycol to polyvinylidene fluoride is 0.08), after 2 hours of stirring and dissolving, spray drying is performed to prepare powder. The spray drying parameters are set to a solution feed rate of 500ml / h, an inlet pressure of 0.08MPa, an inlet speed of 60L / min, and a dryer inlet air temperature of 80 degrees Celsius.
[0135] The prepared surface ligand-perovskite / polymer powder is bright green. 5g of powder was dried at 70°C for 2 hours, and then coated by atomic layer deposition. The powdered product was placed in the reaction chamber of the ALD equipment, and the rotation stirring (speed of 40r / min) was controlled while vacuuming (vacuum degree of 1torr), and then the chamber was heated to 70 degrees Celsius; gaseous titanium tetrachloride was introduced into the powder reaction chamber for 10 seconds to allow it to fully contact and adsorb with the powder surface, and then inert gas was passed to remove excess titanium tetrachloride and by-products for 60 seconds; gaseous water was introduced into the cavity for 10 seconds to react with the titanium tetrachloride on the surface of the particles. At this time, the two precursors reacted to generate the first atomic layer. The operation was repeated for 200 cycles to obtain a powder coated with a titanium oxide layer with a thickness of about 4nm.
[0136] Example 4
[0137] In this example, octylamine bromide-MA is selected 0.9 Cs 0.1 The PbBr3 perovskite quantum dot precursor raw material and the matrix polymer polyvinylidene fluoride and the water-absorbing functional resin sodium polyacrylate were spray dried. 0.55g of the quantum dot material precursor raw material (composed of MABr, CsBr, PbBr2, octylamine bromide, with a molar ratio of 0.9mmol: 0.1mmol: 1mmol: 0.3mmol) was dissolved in 300ml of N, N dimethylformamide, and then 30g of polyvinylidene fluoride and 5g of sodium polyacrylate were added to form a precursor solution (that is, the mass ratio of sodium polyacrylate and polyvinylidene fluoride added was 0.16). After 2 hours of stirring and dissolving, spray drying was performed to prepare powder. The spray drying parameters were set as a solution feed rate of 500ml / h, an inlet pressure of 0.08MPa, an inlet speed of 60L / min, and a dryer inlet air temperature of 90 degrees Celsius.
[0138] The prepared surface ligand-perovskite / polymer powder is bright green. 20g of powder was dried at 70℃ for 2 hours, and then coated by atomic layer deposition. The powdered product was placed in the reaction chamber of the ALD equipment, and the rotation stirring (speed of 50r / min) was controlled while vacuuming (vacuum degree of 1torr), and then the chamber was heated to 85 degrees Celsius; gaseous tetrakis(dimethylamino)zirconium was introduced into the powder reaction chamber for 20 seconds to allow it to fully contact and adsorb with the powder surface, and then inert gas was passed to remove excess tetrakis(dimethylamino)zirconium and by-products for 80 seconds; gaseous water was introduced into the cavity for 20 seconds to react with the tetrakis(dimethylamino)zirconium on the particle surface, and the two precursors reacted to generate the first atomic layer. The operation was repeated for 200 cycles to obtain a powder coated with a zirconium oxide layer with a thickness of about 10nm.
[0139] Example 5
[0140] In this embodiment, tetrabutylammonium iodide-MAPbI3 perovskite quantum dot precursor raw materials and matrix polymer polymethyl methacrylate and water-absorbing functional resin polyethylene glycol are selected for spray drying. 0.8g of quantum dot material precursor raw materials (composed of MAI, PbI2, tetrabutylammonium iodide, molar ratio of 1mmol: 1mmol: 0.5mmol) are dissolved in 300ml of N, N dimethylformamide, and then 20g of polymethyl methacrylate and 1g of polyethylene glycol are added to form a precursor solution (that is, the mass ratio of polyethylene glycol to polymethyl methacrylate is 0.05). After 2 hours of stirring and dissolving, spray drying is performed to prepare powder. The spray drying parameters are set as a solution feed rate of 500ml / h, an inlet pressure of 0.08MPa, an inlet speed of 60L / min, and a dryer inlet air temperature of 90 degrees Celsius.
[0141] The prepared surface ligand-perovskite / polymer powder is bright red. 10g of powder was dried at 70℃ for 2 hours, and then coated by atomic layer deposition. The powdered product was placed in the reaction chamber of the ALD equipment, and the rotation stirring (speed of 60r / min) was controlled while vacuuming (vacuum degree of 1torr), and then the chamber was heated to 70 degrees Celsius; gaseous trimethylaluminum was introduced into the powder reaction chamber for 10 seconds to allow it to fully contact and adsorb with the powder surface, and then inert gas was passed to remove excess trimethylaluminum and by-products for 60 seconds; gaseous water was introduced into the cavity for 10 seconds to react with the trimethylaluminum on the surface of the particles. At this time, the two precursors reacted to generate the first atomic layer. The operation was repeated for 300 cycles to obtain Al2O3-coated powder with a thickness of about 60nm.
[0142] Example 6
[0143] In this embodiment, octylamine iodine / hydrobromic acid-MAPb(Br / I)3 perovskite quantum dot precursor raw materials and matrix polymer polymethyl methacrylate and water-absorbing functional resin polyethylene glycol are selected for spray drying, 0.79g surface ligand-perovskite quantum dot material precursor raw materials (composed of MAI, PbI2, octylamine iodine, hydrobromic acid, molar ratio of 1mmol:1mmol:0.5mmol:0.5mmol) are dissolved in 300ml of N, N dimethylformamide, and then 10g polymethyl methacrylate and 1g polyethylene glycol are added to form a precursor solution (that is, the mass ratio of polyethylene glycol to polymethyl methacrylate is 0.1), and after 2 hours of stirring and dissolving, spray drying is performed to prepare powder. The spray drying parameters are set as the feed rate of the solution is 500ml / h, the air intake pressure is 0.08MPa, the air intake speed is 60L / min, and the dryer air intake temperature is 90 degrees Celsius.
[0144] 50g of powder was dried at 70℃ for 2 hours, and then coated by atomic layer deposition. The powdered product was placed in the reaction chamber of the ALD equipment, and the vacuum was evacuated (vacuum degree was 1torr) while controlling the rotation and stirring (speed was 60r / min), and then the chamber was heated to 70 degrees Celsius; gaseous trimethylaluminum was introduced into the powder reaction chamber for 10 seconds to allow it to fully contact and adsorb with the powder surface, and then inert gas was passed to remove excess trimethylaluminum and by-products for 60 seconds; gaseous water was introduced into the chamber for 10 seconds to allow it to fully react with the trimethylaluminum on the surface of the particles, and at this time, the two precursors reacted to generate the first atomic layer. The operation was repeated for 400 cycles to obtain Al2O3-coated powder with a thickness of about 80nm.
[0145] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A functional composite perovskite quantum dot material, characterized in that: The functional composite perovskite quantum dot material comprises powder particles and a metal oxide film; The powder particles contain surface ligands-perovskite quantum dots, matrix polymers and water-absorbing functional resins; The metal oxide film is coated on the surface of the powder particles by atomic layer deposition; The matrix polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride and trifluoroethylene copolymer, polyacrylonitrile, polyvinyl acetate, cellulose acetate, cyanocellulose, polysulfone, aromatic polyamide, polyimide, polycarbonate, polystyrene, polymethyl methacrylate, and polylauryl methacrylate; The water-absorbing functional resin includes at least one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose and sodium polyacrylate; The metal oxide in the metal oxide film includes at least one of Al2O3, TiO2, HfO2, and ZrO2.
2. The functional composite perovskite quantum dot material according to claim 1, characterized in that: The perovskite quantum dots in the surface ligand-perovskite quantum dots have at least one of the structural formulas ABX3, A3B2X9, and A2BX6; the surface ligands in the surface ligand-perovskite quantum dots have the structural formula CX; Wherein A is selected from NH2CHNH2 + 、CH3NH3 + , Cs + , Rb + , K + At least one of; B is selected from Pb 2+ Sn 2+ 、Bi 3+ 、Ti 3+ 、Zn 2+ 、Ni 2+ 、Cd 2+ 、Al 3+ , Mn 2+ , Mn 4+ ,Ge 3+ At least one of; C is selected from an aromatic group or an alkyl organic amine cation having a carbon number of not less than 3; X is selected from Br - ,I - 、SCN - , and at least one of carboxylate.
3. The functional composite perovskite quantum dot material according to claim 1, characterized in that: The powder particles are obtained by the following steps: Atomizing a powder particle precursor solution into small droplets, and then drying the atomized small droplets to generate powder particles; The powder particle precursor solution comprises a solvent, a surface ligand-perovskite quantum dot precursor raw material, a matrix polymer, and a water-absorbing functional resin.
4. The functional composite perovskite quantum dot material according to claim 3, characterized in that: The solvent includes at least one of dimethyl sulfoxide, n-hexane, cyclohexane, n-octane, octadecene, ethanol, methanol, trimethyl phosphate, triethyl phosphate, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, isopropanol, ethyl acetate, toluene and acetone.
5. The functional composite perovskite quantum dot material according to claim 3, characterized in that: The surface ligand-perovskite quantum dot precursor raw material includes AX, BX m and CX; Wherein A is selected from NH2CHNH2 + 、CH3NH3 + , Cs + , Rb + , K + At least one of; B is selected from Pb 2+ Sn 2+ 、Bi 3+ 、Ti 3+ 、Zn 2+ 、Ni 2+ 、Cd 2+ 、Al 3+ , Mn 2+ , Mn 4+ ,Ge 3+ At least one of; C is selected from an aromatic group or an alkyl organic amine cation having a carbon number of not less than 3; X is selected from Br - ,I - 、SCN - , carboxylate; m=2, 3 or 4.
6. The functional composite perovskite quantum dot material according to claim 5, characterized in that: AX, BX m The molar ratio of CX is 0.5-10:1:0.3-10.
7. The functional composite perovskite quantum dot material according to claim 5, characterized in that: In the powder particle precursor solution, the volume mass ratio of the solvent to the matrix polymer is 300 ml: 1 to 50 g; The mass ratio of the surface ligand-perovskite quantum dot precursor raw material to the matrix polymer is 0.01-1:1-100; The mass ratio of the water-absorbing functional resin to the matrix polymer is 0.02-2.
8. The functional composite perovskite quantum dot material according to claim 3, characterized in that: The conditions for the atomization include: Solution feed rate: 50~50000ml / h; The corresponding atomizer air intake pressure is 0.02-1MPa, and the air intake speed is 15-100L / min.
9. The functional composite perovskite quantum dot material according to claim 3, characterized in that: Drying conditions include: Inlet air temperature: 50~200℃.
10. The functional composite perovskite quantum dot material according to claim 1, characterized in that: The thickness of the metal oxide film is 1 nm to 200 nm.
11. The functional composite perovskite quantum dot material according to claim 1, characterized in that: The particle size of the powder particles is 0.1 to 50 microns.
12. The method for preparing the functional composite perovskite quantum dot material according to any one of claims 1 to 11, characterized in that: The preparation method comprises the following steps: (S1) introducing a gaseous metal precursor into a reaction chamber containing powder particles for adsorption; (S2) introducing a gaseous oxygen precursor to react; The reaction is an atomic layer deposition reaction to obtain the functional composite perovskite quantum dot material; The metal precursor includes at least one of trimethylaluminum, aluminum trichloride, titanium tetrachloride, titanium isopropoxide, tetrakis(dimethylamino)zirconium, hafnium tetrachloride, hafnium nitrate, and dimethylaminozirconium; The powder particles are obtained by the following steps: Atomizing a powder particle precursor solution into small droplets, and then drying the atomized small droplets to generate powder particles; The powder particle precursor solution comprises a solvent, a surface ligand-perovskite quantum dot precursor raw material, a matrix polymer, and a water-absorbing functional resin.
13. The preparation method according to claim 12, characterized in that: The oxygen precursor includes at least one substance containing an oxygen element.
14. The preparation method according to claim 12, characterized in that: The oxygen precursor includes at least one of water, ozone and oxygen.
15. The preparation method according to claim 12, characterized in that: The temperature in the reaction chamber is 40-100° C., and the vacuum degree is 0.1-300 Torr.
16. The preparation method according to claim 12, characterized in that: The time of the adsorption and the reaction are independently 5 to 60 seconds.
17. The preparation method according to claim 12, characterized in that: The adsorption is static adsorption.
18. The preparation method according to claim 12, characterized in that: During the adsorption and reaction process, the powder is dispersed by at least one of rotating, stirring and vibrating the bin.
19. The preparation method according to claim 12, characterized in that: After the adsorption is completed, the following steps are also included: introducing a carrier gas to flush out the remaining precursor and by-products.
20. The preparation method according to claim 19, characterized in that: The carrier gas includes at least one of inert gases.
21. The preparation method according to claim 19, characterized in that: The carrier gas is introduced for 10 to 60 seconds.
22. The preparation method according to claim 12, characterized in that: Repeat steps (S1) to (S2) 1 to 500 times.
23. Application of the functional composite perovskite quantum dot material described in any one of claims 1 to 11 or the functional composite perovskite quantum dot material prepared by the preparation method described in any one of claims 12 to 22 in the fields of backlight display, Micro / Mini LED direct display, lighting or photovoltaic light conversion materials.
Citation Information
Patent Citations
Multi-layer-coated quantum dot beads
CN105051152A
Multilayer structure and preparation method and application thereof
CN110305348A